Late Holocene climate development of Bjørnøya, Svalbard, based on chironomid analysis - Kivilä, Henriikka (Helsingfors universitet, 2014)
Recent climate related changes in the Arctic have risen concern and interest to better understand the mechamisms of arctic climate system and to predict the future response. Due to short instrumental monitoring a palaeoenvironmental view is required to reveal and understand long-term changes, yet high-resolution palaeoecological and -climatological studies are sparse. Bjørnøya, the Bear Island, (74°30' N, 19° E) is a key site for terrestrial palaeoclimate records along the heat transport system of the North Atlantic Current, with the possibility of linking records from northern Fennoscandia and Arctic Svalbard. A summer temperature series for the past ca. 1000 years was reconstructed from a 64 cm surface sediment core from lake Ellasjøen, SW Bjørnøya, based on quantitative palaeoenvironmental modelling of subfossilized chironomid assemblages. Quality of reconstructions was assessed with modern analogue technique and principal component analysis. To support the interpretation and receive a more holistic view of the lake history, in- lake processes, catchment interaction and factors behind the changes, a multi-proxy approach was chosen. Sediment physical characteristics: water content, loss-on-ignition, magnetic susceptibility and spectrocolorimetric identification of sedimentary signatures and components, in addition to composition and diversity of the chironomid assemblage, were used to trace a comprehensive picture of past changes. Radiometric dating was conducted to assess the temporal context of the sedimentary series. The results reveal that Ellasjøen is a climatically sensitive lake and preserves a history of substantial changes. A general pattern is detected where Medieval Warm Period features very modest warmth, followed by warming summer temperatures until 1600 AD, when the temperature trend starts to decrease towards culmination of the Little Ice Age at 1740 AD. A warming trend ever since is persistent but does not exceed past warmth. Results suggest higher seasonality during Little Ice Age and seek to ...